Nature via nurture : genes, experience, and what makes us human - Ridley, Matt. (New York : HarperCollins, 2003)
Documents the 2001 discovery that there are fewer genes in a human genome than previously thought and considers the argument that nurture elements are also largely responsible for human behavior.
Includes bibliographical references (p. [283]-306) and index.
Keywords: Nature and nurture; Human genetics